Coronary artery calcium, HIV and inflammation in Uganda compared with the USA. Issue 1 (22nd May 2019) - Alencherry, Ben; Erem, Geoffrey; Mirembe, Grace; Ssinabulya, Isaac; Yun, Chun-Ho; Hung, Chung-Lieh; Siedner, Mark J; Bittencourt, Marcio; Kityo, Cissy; McComsey, Grace A; Longenecker, Chris T
Abstract : Objectives: To compare the prevalence of detectable coronary artery calcium (CAC) among higher risk, older people living with HIV (PLWH) and uninfected persons in Uganda versus the USA, and second to explore associations of CAC with HIV-specific variables and biomarkers of inflammation. Methods: This cross-sectional study of 430 total subjects compared 100 PLWH on antiretroviral therapy and 100 age-matched and sex-matched HIV-uninfected controls in Uganda with 167 PLWH on antiretroviral therapy and 63 uninfected controls in the USA. Multivariable logistic regression was used to examine associations with detectable CAC (CAC >0). Results: Compared with US subjects, Ugandans were older (mean age 56 vs 52 years) and were more likely to have diabetes (36% vs 3%) and hypertension (85% vs 36%), but were less likely to be male (38% vs 74%) or smokers (4% vs 56%). After adjustment for HIV serostatus, age, sex and traditional risk factors, Ugandans had substantially lower odds of CAC >0 (adjusted OR 0.07 (95% CI 0.03 to 0.17), p<0.001). HIV was not associated with CAC >0 in either country (p>0.1). Among all PLWH, nadir CD4 count was associated with the presence of CAC, and among Ugandans soluble intercellular adhesion molecule (p=0.044), soluble CD163 (p=0.004) and oxidised low-density lipoprotein (p=0.043) were all associated with the presence of CAC. Conclusions: Ugandans had a dramatically lower prevalence of any coronary calcification compared with US subjects. The role of HIV infection and inflammation as risk factors for subclinical coronary disease in sub-Saharan Africa merits further investigation.